2020
DOI: 10.1177/0300060519871407
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of natural killer cells in the pathogenesis of endometriosis in patients with pelvic pain

Abstract: Objectives To detect the involvement of immune cells in the pathogenesis of endometriosis in patients with stable status or pelvic pain. Methods Blood was collected from patients with endometriosis with and without pelvic pain. Natural killer (NK) and Th17 cells were analyzed by flow cytometry, and secretion of inflammatory cytokines (tumor necrosis factor-α, interleukin (IL)-1β, IL-6, IL-7) was verified by enzyme-linked immunosorbent assay. We isolated immune cells from blood by density-gradient centrifugatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“… 18 The levels of NK cells in the peripheral blood were significantly higher in endometriosis patients with pelvic pain compared with women with stable disease without pelvic pain. 40 In both physiological and pathological conditions, peripheral nociceptive (including pruriceptive) neurons may express a variety of immune-related receptors, such as chemokine receptors and immunoglobulin (Fc) receptors that are usually found on immune cells. 41 Certain ligands such as chemokines and immune complexes may induce abnormal neuronal hyperexcitability and even the discharge of ectopic action potentials, thus producing the sensation of pain, discomfort, or itch in immune-related disease.…”
Section: Discussionmentioning
confidence: 99%
“… 18 The levels of NK cells in the peripheral blood were significantly higher in endometriosis patients with pelvic pain compared with women with stable disease without pelvic pain. 40 In both physiological and pathological conditions, peripheral nociceptive (including pruriceptive) neurons may express a variety of immune-related receptors, such as chemokine receptors and immunoglobulin (Fc) receptors that are usually found on immune cells. 41 Certain ligands such as chemokines and immune complexes may induce abnormal neuronal hyperexcitability and even the discharge of ectopic action potentials, thus producing the sensation of pain, discomfort, or itch in immune-related disease.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that the AA genotype of IL‐12B rs3212227 was associated with the decreased risk of uterus involvement in endometriosis patients. The mechanism of this association is not clear; however, as A) IL‐12 is important for NK cell activation and functionality (Zwirner & Ziblat, 2017) B) uterus harbours specific subsets of NK cells (Strunz et al., 2021) C) and recent studies have highlighted the importance of NK cells in the pathogenesis of endometriosis (He et al., 2020; Ścieżyńska et al., 2019), we propose that there might be a link between the aforementioned SNP and NK cell functionality in the context of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone is an essential hormone that may be given orally or applied topically for pregnancy maintenance [101][102][103]. NK cells do not have receptors for this hormone; however, T cells do [102][103][104]. The factor induced by progesterone, PIBF, generates a tolerogenic TH2 response in the endometrium and consequently may affect NK cell migration and response [105].…”
Section: Progesteronementioning
confidence: 99%